BASIC MECHANICS OF FREEZING, FROZEN AND THAWING SOILS (OSNOVY MEKHANIKI PROMERZAYUSHCHIKH, MERZLYKH I PROTAIVAYUSHCHIKH GRUNTOV). - Tsytovich,N. A. (1966)
The mechanics of freezing soils are discussed with respect to change in soil volume, frost heaving, and rejection of water from soil during freezing. The physical properties of freezing soil and ice are reviewed. This is followed by a discussion of the mechanical properties of frozen soil including mechanical bonds, deformation characteristics and compaction under load. The rheological processes in frozen soils are considered in connection with their relation to short-term and long-term loads. The report concludes with a discussion of the stresses and deformation occurring in thawing soils. (Author) Trans. of mono. Osnovy Geokriologii (Merzlotovedeniya), Chast vtoraya, Inzhenernaya Geokriologiya Moscow, 1959 p28-79.